Rainbow scarab Phaneaus vindex Macleay (Insecta: Coleoptera: Scarabaeidae) - Thomson Paris; Barukh Rohde; Phillip E. Kaufman (EDIS)
Rainbow scarabs are members of the beetle family Scarabaeidae, which along with the family Geotrupidae, are commonly known as dung beetles. Scarab beetles were the objects of worship in Ancient Egypt and the more spectacular varieties are made into jewelry. The genus Phanaeus MacLeay is distributed primarily in Neotropical habitats with 100 species, but also in the Neartic region with nine species and the West Indies with one. Dung beetles serve an important role in pasture ecosystems, which has resulted in their introduction around the world. The rainbow scarab has a bright exterior of metallic green, blue, and red interspersed with golden reflections. This 5-page fact sheet was written by Thomson Paris, Barukh Rohde, and Philip E. Kaufman, and published by the UF Department of Entomology and Nematology, July 2013.